Penerapan Problem Based Learning dalam Meningkatkan Hasil Belajar dan Cara Berpikir Kritis Siswa SMA pada Pelajaran Biologi - Azura, Riska Multi; Selaras, Ganda Hijrah (ANWARUL, 2023)
This study aims to determine the effect of the Problem Based Learning (PBL) learning model in improving learning outcomes and critical thinking of high school students in biology subjects. The data collection technique was carried out by searching for articles through Google Scholar, Garuda and Sinta. From the search results, 25 National Journals were obtained that met the specified inclusion criteria. The analysis applied is by paying attention to the score before the test or pretest of Problem Based Learning (PBL) learning with after the PBL learning action with the score before the test or posttest as the amount of increase in the pretest process, then dividing the score before the learning action using the PBL model to determine the size influence on PBL learning actions. Based on the results of the analysis of the PBL learning model, it succeeded in having a positive impact. For an effect size of 0.52 with a strong category. The conclusion of this study is that the problem-based learning or PBL method in increasing knowledge and critical thinking of high school students in biology subjects can increase learning outcomes from the lowest 01.03% to the highest 97.43%. This clearly shows that the use of the PBL method in teaching and learning activities can improve learning outcomes and critical thinking of high school students in biology learning in high school.